SOURCES OF INNOVATIVENESS IN TOURISM - Wszendybył-Skulska, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2010)
In knowledge-based tourist economy innovativeness becomes one of the key pivots in competitiveness growth for various economies as well as in reaching a permanent competitive advantage [Borkowska 2008]. Global competitiveness constitutes a pressure factor to improve innovative ability [Porter 2001] by tourist businesses or companies that face the necessity of taking various actions tending to be oriented towards the present and future. Only such action proves they will stay on the market longer. Tourist businesses vary in view of a level of innovativeness subject to the approved action strategy, type of activity, workforce qualifications, market environment, etc. Innovations may and are affected by all employees, customers, deliverers and all those who are interested. Thus, examination of all transitions on the market when it comes to the extent of utilization of particular sources of innovativeness in the process of improvement in offers given by tourist businesses in Poland deems to be significant. The main aim of the article is to point out which of the sources are most often used in innovative activities of tourist businesses in Poland.